PENGGUNAAN RUMPUT LULANGAN (Eleusine Indica L.) DAN BIOCHAR SEBAGAI AGEN FITOREMIDIASI TANAH TERCEMAR - Aman, Hadrianus; Hamzah, Amir; Triana, Hesti (Universitas Tribhuwana Tunggadewi, 2016)
The advantages of phytoremediation in addition to being easy is also a cheap alternative compared to physical-chemical remediation and bioremediation using microorganisms . This study uses three types of plants that have been previously identified, the three types of plants are L replication, Akarwangi, P Turn the power off. This research was conducted in Sumber Brantas Village, Batu City at an altitude of 1,500 m asl. The research was carried out in two series, namely the first series covering, taking soil samples for analysis of heavy metals, while the second series planting Lulang grass as a phytoremidiation agent. This research is an integral part of PPT research in 2017 . This study uses three types of plants that have been previously identified, the three types of plants are L replication, Akarwangi, P Turn the power off. Observation of plant growth which includes :high plant (cm), amount leaf ( strands ), amount tillers ( tillers ) and weight stover (g) and p gathering is the root (cm). The results of the observational parameter data in this study used Diskptive analysis. Based on the analysis it is concluded that t anaman lulangan able to accumulate heavy metals cadmium in contaminated soil with trial type biochar under review from growth high plant amounting to 52.18 cm, the amount puppies as much as 43.89 tillers, length root 32.89 cm on biochar crooked tobacco + husk rice , heavy root 3.71 g on biochar crooked tobacco and weight leaf amounting to 30.22 g. Keuntungan fitoremediasi selain mudah juga merupakan alternatif yang murah dibandingkan dengan cara remediasi fisik-kimia maupun bioremediasi yang menggunakan mikroorganisme. Penelitian ini menggunakan tiga jenis tanaman yang telah di identifikasi sebelumnya ketiga jenis tanaman itu adalah Lulangan, Akarwangi, Patikan. Penelitian ini di laksanakan di Desa Sumber Brantas Kota Batu pada ketinggian 1.500 m dpl. Penelitian di laksanakan dalam dua seri yaitu seri pertama meeliputi, pengambilan sampel tanah untuk di analisis logam berat, sedangkan seri kedua penanaman rumput lulangan sebagai agen fitoremidiasi. Penelitian ini merupakan bagian yang tak terpisahkan dari penelitian PPT tahun 2017. Akarwangi, Patikan. Pengamatan pertumbuhan tanaman yang di meliputi : tinggi tanaman (cm), jumlah daun (helai), jumlah anakan (anakan) dan berat brangkasan (g) dan panjang akar (cm). Data hasi parameter pengamatan dalam penelitian ini menggunakan analisis Diskrptif. Berdasarkan hasil analisis dapat disimpulkan bahwa tanaman lulangan mampu mengakumulasi logam berat kadmium dalam tanah yang tercemar dengan percobaan jenis biochar yang ditinjau dari pertumbuhan tinggi tanaman sebesar 52,18 cm, jumlah anakan sebanyak 43,89 anakan, panjang akar 32,89 cm pada biochar jengkok tembakau + sekam padi, berat akar 3,71 g pada biochar jengkok tembakau dan berat daun sebesar 30,22 g.